Antibiotics and RNase P - Denis Drainas (MDPI AG, 2016)
RNase P is an essential endonuclease in tRNA biogenesis, which generates the mature 5'-termini of tRNAs. Most forms of RNase P are ribonucleoproteins, i.e., they consist of an essential RNA and protein subunits. The catalytic function of ribonucleoprotein RNase P enzymes resides entirely in the RNA subunit. Its high structural and functional diversity among representatives of a vast variety of phylogenetic domains indicates that RNase P could serve as a molecular target and a useful screening system for the development of new drugs in the battle against bacterial drug resistance.